2021
DOI: 10.1002/mde.3364
|View full text |Cite
|
Sign up to set email alerts
|

Online channel introduction under contract negotiation: Reselling versus agency selling

Abstract: This study investigates manufacturers' online channel introduction strategies by considering two typical retailing formats, namely, reselling and agency selling. Online spillover effect and contract negotiation are considered to make the model more consistent with practice. We find that with a strong bargaining power, the manufacturer will always be profitable when it introduces online channels, whether it is reselling or agency selling. Meanwhile, agency selling is always profitable for the manufacturer than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…The spillover effect indicates how the spread of buying behaviors between online and offline channels significantly influences manufacturers’ expectations and decisions in choosing channels. Chen et al ( 2021 ) explored how a manufacturer’s bargaining power and the online spillover effect can positively or negatively influence the introduction of an online channel. They inferred that reselling will be unprofitable when the online spillover effect is significant, and the manufacturer has weak bargaining power.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…The spillover effect indicates how the spread of buying behaviors between online and offline channels significantly influences manufacturers’ expectations and decisions in choosing channels. Chen et al ( 2021 ) explored how a manufacturer’s bargaining power and the online spillover effect can positively or negatively influence the introduction of an online channel. They inferred that reselling will be unprofitable when the online spillover effect is significant, and the manufacturer has weak bargaining power.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Their analysis demonstrated that in a dual-channel setting, the reselling model dominates when both customer channel preference and commission rate are relatively high, whereas the agency model dominates when the customer channel preference is relatively high (resp., low) and the commission rate is relatively small (resp., large). Chen et al (2021) showed that when the supplier introduces an online retailer channel in addition to an offline direct channel, it is always profitable to adopt the agency model, whereas the retailer always prefers the reselling model. Feng et al (2020) examined the impact of the rental online marketplace in the luxury fashion rental industry from both the supplier's and the platform's perspectives.…”
Section: Business Model Choicementioning
confidence: 99%
“…7 The OR purchases products from upstream suppliers with a wholesale price and sells via the EP with a retail price . The EP charges a platform usage fee rate from the OR (Chen et al, 2021 ; Wang et al, 2019 ). Therefore, the EP acts as an agency seller and his revenue comes from sharing the OR’s revenue.…”
Section: Model Formulationmentioning
confidence: 99%